2006
DOI: 10.1002/jbm.b.30669
|View full text |Cite
|
Sign up to set email alerts
|

Deep rolling of titanium rods for application in modular total hip arthroplasty

Abstract: Compressive residual stresses are commonly introduced into the near-surface regions of morse taper junctions of modular hip endoprostheses to prolong fatigue life. An increasing number of publications report that contamination of shot-peened surfaces can lead to enhanced corrosion and third body wear. This study evaluates deep rolling of titanium alloy rods as a possible alternative to shot peening. Ten rods of Ti6Al7Nb alloy with a diameter of 15 mm were deep rolled with various rolling parameters. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…Thus, the final shot peening process using glass beads that have been applied subsequently to the shot peening by cut wire and the laser shock peening may be one option for cleaning when it is guaranteed that glass contamination is minimized to avoid increased wear due to hard foreign particles (third body wear) [ 39 , 40 ]. Deep rolling was proposed as a suitable alternative to the peening treatment on a medical grade Ti6Al7Nb alloy resulting in beneficial residual stress depth distributions with its maximum of compressive residual stresses below the surface and no contaminations at the surface [ 29 ]. However, since the basic loading mode of the hip junction is bending, the highest compressive residual stresses are expected to minimize crack initiation at the very surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the final shot peening process using glass beads that have been applied subsequently to the shot peening by cut wire and the laser shock peening may be one option for cleaning when it is guaranteed that glass contamination is minimized to avoid increased wear due to hard foreign particles (third body wear) [ 39 , 40 ]. Deep rolling was proposed as a suitable alternative to the peening treatment on a medical grade Ti6Al7Nb alloy resulting in beneficial residual stress depth distributions with its maximum of compressive residual stresses below the surface and no contaminations at the surface [ 29 ]. However, since the basic loading mode of the hip junction is bending, the highest compressive residual stresses are expected to minimize crack initiation at the very surface.…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly the reference material for further developments, such as new titanium based alloys or carbon fiber reinforced PEEK [ 27 ]. (d) Final surface modifications : beside thermal treatments, mechanical surface treatments enhance the fatigue and cyclic deformation behavior of titanium alloys and have already been applied in parts within the scope of biomedical applications [ 28 , 29 ]. From other engineering disciplines, they are known to strengthen the substrate without changing the material’s composition [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denkena et al [12] tried to control the corrosion of the Mg-Ca3.0 implant by mechanical treating the implant surface using DR technique and ultimately to achieve adaptable degradation profile for various medical applications. As compared to shot peening, LPB/DR avoids the contamination of the processed surfaces and consequently prevents the third body wear [53]. Besides, LPB/DR produces higher and deeper compressive residual stresses with less amount of clod work [49,54].…”
Section: Ca Alloying and Surface Treatment Processesmentioning
confidence: 99%
“…For example, after the rolling burnishing of Ti-2.5Cu alloy, a strain-hardened layer was obtained, which was about 3 times deeper than the layer produced by shot peening [13]. Effects of roller burnishing depend to a large extent on technological conditions, as confirmed by the investigation of TiAl6Nb7 alloy [14] and tool design [15]. The authors of the study [16] have found that the combined use of roller burnishing and nitriding on the samples made of titanium alloy Ti-6Al-5Mo-5V-1, 5Cu-1Fe (according to Russian standards VT22) leads to higher wear resistance of these samples in contact with Cu-10Al-4Ni-4Fe counter-samples.…”
Section: Introductionmentioning
confidence: 73%